2019
DOI: 10.1016/j.scienta.2019.108589
|View full text |Cite
|
Sign up to set email alerts
|

Infection risk of Monilinia fructicola on stone fruit during cold storage and immersion in the dump tank

Abstract: Monilinia spp. is the main pathogen responsible for postharvest losses of stone fruit.Several studies have examined the conditions for Monilinia spp. infection in the field, but very limited information is available about postharvest. Storing fruit for 24 hours in cold room and water dump fruit in a water tank are the most common handling operations during the postharvest of fruit. Then, the aim of this study was to investigate the risk of Monilinia fructicola infection for peaches and nectarines during cold s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…Monilinia growth was very low at 0 °C. M. fructicola conidia on fruit surface at 0 °C and 100% RH or 4 °C and 100% RH for up to 30 d caused a very low risk of infection, with only a 3.3% and 3.8% brown rot rate of incidence, respectively [ 26 ]. Monilinia spp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Monilinia growth was very low at 0 °C. M. fructicola conidia on fruit surface at 0 °C and 100% RH or 4 °C and 100% RH for up to 30 d caused a very low risk of infection, with only a 3.3% and 3.8% brown rot rate of incidence, respectively [ 26 ]. Monilinia spp.…”
Section: Discussionmentioning
confidence: 99%
“…development and their latent infections, although it is also dependent on relative humidity (RH), wetness duration, and water availability [ 9 , 21 , 39 , 41 ]. During stone fruit postharvest, humidity must be well controlled and kept constant at 60% in order to avoid new brown rot infections, although at this relative humidity, fruit would lose its firmness and quality, reducing their shelf life [ 26 ]. Previously, we reported that high relative humidity levels increase the number of active infections by M. fructicola and especially M. laxa conidia in in vitro experiments [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the two species significantly differ in infection and colonization speed, whereby M. fructicola is more aggressive, causing larger fruit lesions and having shorter periods of both incubation and latency [37]. However, the risk of Monilinia infection is significantly reduced at low temperatures [38].…”
Section: Environmentmentioning
confidence: 99%